The Impact Of Business Strategies On The Company's Performance: A Case Study Of Multi Communications Sdn. Bhd. - Kamaruddin, Norshida (2001)
Multi Communications Sdn Bhd was established on 1 July 1992 with the principal activity of investment holding in telecommunications.This case study has been prepared using several tools like SWOT analysis, Financial Performance Review analysis and etc to analyze the Company's performance and its business strategies with the purpose of gaining an understanding of the group operations and business strategies.